2007
DOI: 10.1002/jat.1301
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes associated with altered growth and differentiation in benzo[a]pyrene or arsenic exposed normal human epidermal keratinocytes

Abstract: Both arsenic and benzo[a]pyrene (BaP) inhibit terminal differentiation and alter growth potential in normal human epidermal keratinocytes (NHEK) in vitro. To identify molecular alterations that may be involved in these cellular processes, microarray analysis was carried out on NHEK treated with BaP or arsenic. The gene expression microarray results measuring mRNA levels were as follows: (1) in total, the expression of 85 genes was induced and 17 genes was suppressed by 2.0 microm BaP. (2) Arsenic at an equitox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Microarray studies of MMA III ‐ and DMA III ‐exposed NHEKs are lacking in the literature, but many of the transcription trends previously reported in iAs III ‐exposed NHEKs under similar experimental conditions are consistent with those observed in this study [42, 47, 48]. These gene expression results have indicated that in the skin, sustained ROS production and subsequent activation of key signaling pathways that control apoptosis, inflammation, differentiation, and proliferation (especially NF‐κB and MAPK pathways), growth factor overproduction, transcriptional downregulation of DNA repair genes, and therefore decreased DNA repair capacity may play important roles in iAs skin carcinogenesis [19, 46–49, 62, 63]. Comprehensive analyses of gene expression profiles associated with trivalent or pentavalent iAs exposure in a variety of in vitro and in vivo models indicate similar transcriptional alterations occur in a variety of cell types and that several concurrent events (i.e., increased cellular proliferation, chronic exposure to oxidative stress, chronic inflammation, loss of cell‐cycle control, and decreased capacity for DNA repair) may be key driving forces behind iAs carcinogenesis in all target cells [64].…”
Section: Discussionsupporting
confidence: 89%
“…Microarray studies of MMA III ‐ and DMA III ‐exposed NHEKs are lacking in the literature, but many of the transcription trends previously reported in iAs III ‐exposed NHEKs under similar experimental conditions are consistent with those observed in this study [42, 47, 48]. These gene expression results have indicated that in the skin, sustained ROS production and subsequent activation of key signaling pathways that control apoptosis, inflammation, differentiation, and proliferation (especially NF‐κB and MAPK pathways), growth factor overproduction, transcriptional downregulation of DNA repair genes, and therefore decreased DNA repair capacity may play important roles in iAs skin carcinogenesis [19, 46–49, 62, 63]. Comprehensive analyses of gene expression profiles associated with trivalent or pentavalent iAs exposure in a variety of in vitro and in vivo models indicate similar transcriptional alterations occur in a variety of cell types and that several concurrent events (i.e., increased cellular proliferation, chronic exposure to oxidative stress, chronic inflammation, loss of cell‐cycle control, and decreased capacity for DNA repair) may be key driving forces behind iAs carcinogenesis in all target cells [64].…”
Section: Discussionsupporting
confidence: 89%
“…Perez et al have revealed that BaP exposure (2 mM) for 24 h up-regulated expression of IL-1a using microarray analysis [32]. This result may partly support our data, because IL-1 signaling regulates IL-8 gene expression in NHEKs [33].…”
Section: [ ( ) T D $ F I G ]supporting
confidence: 90%
“…VDAC1 has been found to be involved in the cellular apoptotic response to BaP in mice, rats, and human cell lines (Huc et al, 2007; Andreau et al, 2012). Perez et al (2008) did not find RAD50 expression to be upregulated by BaP exposure in normal human keratinocytes, but Brevik et al (2012) determined that paternal exposure to BaP did up-regulate expression in mouse embryos. In this instance, RAD50 may serve as a biomarker of developmental toxicity and exposure to the toxicant.…”
Section: Discussionmentioning
confidence: 99%